Evaluation of metagenetic community analysis of planktonic copepods using Illumina MiSeq: Comparisons with morphological classification and metagenetic analysis using Roche 454. - Junya Hirai; Satoshi Nagai; Kiyotaka Hidaka (PLoS ONE)
Metagenetics is a rapid and taxonomically comprehensive method for revealing community structures within environmental samples, based on large amounts of sequence data produced by high-throughput sequencers. Because community structures of planktonic copepods are important in the ocean owing to their high diversity and abundance, a metagenetic analysis of the 28S D2 region using Roche 454 was previously developed. However, the Illumina MiSeq platform with a high sequence output is being used more frequently in metagenetics, and non-calanoid copepods have not previously been fully evaluated. Here, we evaluated an Illumina MiSeq-based metagenetic analysis using a mock community and field-collected samples that were examined in a previous study using Roche 454, and the community structure, including non-calanoid copepods, was compared among morphological and metagenetic analyses. We removed a singleton read and applied an appropriate abundance threshold to remove erroneous Molecular Operational Taxonomic Units (MOTUs) with low-abundance sequences in the MiSeq-based analysis. Results showed that the copepod community was successfully characterized using Illumina MiSeq. Higher-quality sequences were obtained using MiSeq than by Roche 454, which reduced the overestimation of diversity, especially at a strict 99% similarity threshold for MOTU clustering. Taxonomic compositions in terms of both biomass and presence/absence of species, including non-calanoids, were more appropriately represented in the MiSeq- than in Roche 454-based analysis. Our data showed that metagenetic analysis using Illumina MiSeq is more useful for revealing copepod communities than Roche 454, owing to the lower cost and higher quality.